2016
DOI: 10.1103/physrevb.94.195410
|View full text |Cite
|
Sign up to set email alerts
|

Optical label-free and model-free probe of the surface potential of nanoscale and microscopic objects in aqueous solution

Abstract: The electrostatic environment of aqueous systems is an essential ingredient for the function of any living system. To understand the electrostatic properties and their molecular foundation in soft, living, and three-dimensional systems, we developed a table-top model-free method to determine the surface potential of nano-and microscopic objects in aqueous solutions. Angle-resolved nonresonant second harmonic (SH) scattering measurements contain enough information to determine the surface potential unambiguousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
161
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 75 publications
(171 citation statements)
references
References 54 publications
(90 reference statements)
10
161
0
Order By: Relevance
“…Candidates for the emission of SH photons are all noncentrosymmetrically structured molecular groups ( 30 , 33 ), that is, lipids or water. Taking into account the number density difference between water and lipids and previous nonresonant SH scattering studies of liposomes ( 34 , 35 ), it is likely that the dominant contribution to the SH intensity will be from water. To test this hypothesis, we added 0.5 mM KCl to the solution.…”
Section: Resultsmentioning
confidence: 99%
“…Candidates for the emission of SH photons are all noncentrosymmetrically structured molecular groups ( 30 , 33 ), that is, lipids or water. Taking into account the number density difference between water and lipids and previous nonresonant SH scattering studies of liposomes ( 34 , 35 ), it is likely that the dominant contribution to the SH intensity will be from water. To test this hypothesis, we added 0.5 mM KCl to the solution.…”
Section: Resultsmentioning
confidence: 99%
“…These assumptions were validated in previous studies. 11,13,25 Although we employ the RGD assumption for the linear interaction, the nonlinear interaction contains a correction to account for the change in field amplitude when the optical electromagnetic fields cross the particle/water interface. Dadap et al showed that a linear correction term to the second-order susceptibility is sufficient to correct for the change in the electromagnetic field when it crosses the interface.…”
Section: F Determining the Surface Potentialmentioning
confidence: 99%
“…9,10 Polarization-and angle-resolved (AR) SHS were recently demonstrated as a method to obtain a unique value for the surface potential of a particle in aqueous solution. 11 Key to this method is the fact that the nonlinear polarization of water at the second harmonic frequency depends linearly on the ensemble electrostatic field in the solution. This ensemble electrostatic field originates from all charges and partial charges (such as dipoles and quadrupoles) in the solution.…”
Section: Introductionmentioning
confidence: 99%
“…However, a second electrolyte concentration-dependent effect has been proposed, based on theoretical considerations and direct observation by second harmonic scattering. 15,23 At very low electrolyte concentrations, the probing depth can be limited by phase matching of the V-SFG probe. Hence, as the penetration depth of the DC field exceeds the coherence length, the signal intensity is expected to be increasingly depleted due to destructive interference between contributions from sufficiently spatially separated non-linear active molecules.…”
Section: 14mentioning
confidence: 99%
“…These values for the w (3) /w (2) ratio seem reasonable compared with previous studies of water at charged surfaces. 20,23 Please note that for simplicity we assume that the charge density is constant for all salt concentrations. Small variation with concentration cannot be excluded as the surface charge density of silica (À0.06 C m À2 o s 0 o À0.02 C m À2 ) 2,4,14,26,27 is typically around the critical surface charge density (s 0,crit ) above which counterion condensation occurs.…”
mentioning
confidence: 99%